Large‐scale patterns of fish diversity and assemblage structure in the longest tropical river in Asia. Issue 4 (31st August 2016) - Chea, Ratha; Lek, Sovan; Ngor, Pengbun; Grenouillet, Gaël
Abstract: Although the Mekong River is one of the world's 35 biodiversity hot spots, the large‐scale patterns of fish diversity and assemblage structure remain poorly addressed. This study aimed to investigate the fish distribution patterns in the Lower Mekong River (LMR) and to identify their environmental determinants. Daily fish catch data (i.e. from December 2000 to November 2001) at 38 sites distributed along the LMR were related to 15 physicochemical and 19 climatic variables. As a result, four different clusters were defined according to the similarity in assemblage composition and 80 indicator species were identified. While fish species richness was highest in the Mekong delta and lowest in the upper part of the LMR, the diversity index was highest in the middle part of the LMR and lowest in the delta. We found that fish assemblages changed along the environmental gradients and that the main drivers affecting the fish assemblage structure were the seasonal variation of temperature, precipitation, dissolved oxygen, pH and total phosphorus. Specifically, upstream assemblages were characterised by cyprinids and Pangasius catfish, well suited to low temperature, high dissolved oxygen and high pH. Fish assemblages in the delta were dominated by perch‐like fish and clupeids, more tolerant to high temperatures, and high levels of nutrients (nitrates and total phosphorus) and salinity. Overall, the patterns were consistent between seasons. Our study contributes to establishing the first holistic fish community study in the LMR.